Aluminum foil with microporous structure and preparation method thereof

Through electrochemical method, micropores are formed on aluminum foil, which solves the problems of high cost of micropore aluminum foil preparation, environmental protection problems and difficult pore size control in the existing technology, and realizes efficient and flexible preparation of micropore aluminum foil, which is suitable for diversified applications. .

CN119320979APending Publication Date: 2025-01-17NANJING LONGDIAN HUAXIN NEW ENERGY MATERIALS IND TECH RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411308871.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing microporous aluminum foil preparation technology has limitations such as high cost, environmental protection problems, difficulty in controlling pore size, difficult processing and low efficiency, which limits its wide application in the battery field.

Method used

Using electrochemical method, aluminum foil is electrolyzed as an anode through a mixed electrolyte of water-soluble additives and salt solutions, micropores are formed using current and voltage, and the additive type, molecular weight, concentration and electrolytic conditions are controlled to accurately regulate the pore size and pore structure.

Benefits of technology

It realizes precise control of microporous aluminum foil, improves production efficiency, shortens production cycle, has flexibility and environmental protection, adapts to diversified market demands, and improves product stability and response speed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320979A_ABST
    Figure CN119320979A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an aluminum foil with a microporous structure. The preparation method comprises the following specific steps: mixing a water-soluble additive and water according to a preset proportion to prepare a water-soluble additive solution I; preparing a salt solution II with a certain concentration; the salt solution II is a salt aqueous solution capable of providing conductive ions; uniformly mixing the solution I and the salt solution II according to a certain proportion to serve as an electrolyte III for preparing the microporous aluminum foil in the next step, and enabling the concentration of the water-soluble additive in the solution to be 1-500ppm after mixing; the original aluminum foil IV is immersed in the electrolyte III to serve as an anode, the conductive material V is immersed in the electrolyte III to serve as a cathode, and current with proper magnitude is loaded for electrolysis; and after electrolysis is conducted for a specific duration, the aluminum foil IV is taken out, cleaned and aired, and the microporous aluminum foil V is obtained. The hole edge of the microporous aluminum foil is in a smooth form, no obvious particles or convex substances exist, and the surface is free of burrs and oxidation; compared with the traditional microporous aluminum foil, the product does not have the quality problems of burrs, oxidation and the like, and the overall quality and reliability of the product are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of metal foil processing, and in particular relates to an aluminum foil with a microporous structure. Background technology:

[0002] Microporous aluminum foil is a kind of aluminum foil with multiple tiny pores formed by special processing, which is widely used in lithium-ion battery and capacitor market. In lithium-ion batteries, microporous aluminum foil is used as a current collector. Compared with traditional aluminum foil, it has the advantages of optimizing electrolyte wettability, improving foil surface adhesion and improving the bending flexibility of the pole piece, thus significantly improving the efficiency and overall performance of the battery.

[0003] In capacitors, microporous aluminum foil acts as an electrode current collector, which can effectively enhance the functionality and performance of capacitors. In addition, microporous aluminum foil can also be used in a variety of applications such as packaging, insulation and filtration. By effectively adsorbing and releasing liquids and gases, it meets the growing demand for lightweight packaging materials and the market demand for sustainable and environmentally friendly products. Its advantages include improved barrier properties, improved heat resistance and recyclability, which further promotes the growth of the market.

[0004] However, the existing several technical methods for preparing microporous aluminum foil have their own limitations. For example, the chemical etching method removes part of the material on the surface of the aluminum foil through chemical reaction to form micropores. Although the cost is low, it has disadvantages such as solution complexity, environmental issues and difficulty in pore size control; mechanical processing methods include physical processing methods such as stamping and drilling. Although holes can be formed directly on the aluminum foil, burrs are easily generated, the processing is difficult and the efficiency is low; laser processing methods use high-energy laser beams to quickly evaporate materials on the aluminum foil to form holes. Although the pore size is controllable and the processing speed is fast, it may cause oxidation of the aluminum foil surface, high cost and heat-affected zone. These limitations restrict the widespread application of microporous aluminum foil in the battery field.

[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention:

[0006] The object of the present invention is to provide an aluminum foil with a microporous structure, thereby overcoming the defects in the above-mentioned prior art.

[0007] To achieve the above object, the present invention provides a method for preparing an aluminum foil with a microporous structure, characterized in that the specific steps are as follows:

[0008] a. A water-soluble additive and water are mixed in a predetermined ratio to prepare a water-soluble additive solution I, wherein the water-soluble additive solution I contains macromolecules and small molecules having amino, hydroxyl, thiol, carboxyl, ether bond, aldehyde, and nitrogen-containing functional groups, wherein the macromolecule refers to a molecule having a molecular weight greater than 1000, and the small molecule refers to a molecule having a molecular weight less than 1000;

[0009] b. Prepare a salt solution II of a certain concentration; the salt solution II is a salt aqueous solution that can provide conductive ions, selected from one of sodium chloride, potassium bromide, potassium perchlorate, and potassium sulfate; or a compound that can react with Al, selected from one of cupric chloride, ferric chloride, potassium hydroxide, hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, formic acid, oxalic acid, and chloroacetic acid;

[0010] c. Mixing solution I and salt solution II in a certain proportion to form electrolyte III for preparing microporous aluminum foil in the next step, wherein the concentration of the water-soluble additive in the solution is 1-500 ppm after mixing;

[0011] d. Immerse the original aluminum foil IV in the electrolyte III as an anode, immerse the conductive material V in the electrolyte III as a cathode, and load an appropriate current for electrolysis;

[0012] e. After electrolysis for a specific period of time, the aluminum foil IV is taken out, cleaned and dried to obtain a microporous aluminum foil.

[0013] When aluminum foil is immersed in solution III, the additive molecules can be adsorbed on the surface of the foil. Additives with larger molecular weights can be evenly adsorbed on the surface of aluminum by virtue of functional groups such as hydroxyl, amino, carboxyl, and thiol. Additives with smaller molecular weights can be adsorbed with macromolecules to supplement the surface space of the foil, thereby achieving coverage of the foil surface. During electrolysis, the foil acts as an anode. Under the action of an applied current / voltage, aluminum loses electrons to generate aluminum ions, and the additive coverage on a small part of the foil surface is destroyed, thereby generating holes. When the solution contains Cl - 、F - When there are anions, these ions have a small radius and strong penetration, which can easily destroy the oxide film and produce corrosion holes. By controlling the type, molecular weight, concentration of additives, as well as the electrolyte composition, concentration, pH, temperature, current density, voltage and electrolysis time, microporous aluminum foil with different pore sizes and pore structures can be obtained.

[0014] The pore size is related to the molecular weight and concentration of the additive. The larger the molecular weight and the higher the concentration, the smaller the pore size. The pore depth is related to the concentration of ions in the solution, temperature, reaction time, and current / voltage. The greater the ion concentration, the higher the temperature, the longer the reaction time, and the higher the current / voltage, the deeper the pore depth. The pore density is related to the additive concentration, the salt ion concentration, and the current / voltage. The smaller the additive concentration, the higher the salt ion concentration and the current / voltage, the greater the pore density. The higher the concentration of H+, OH- or oxidizing ions such as Cu2+, the faster the reaction rate.

[0015] The concentration of ions reacting with Al in the solution and the size of the applied current / voltage are related to the degree of damage to the additive coverage. When the total concentration of ions that can react with Al in the solution is 0.01mol / L-5mol / L and the applied current density is 1-15A / dm2, 0.2%-30% of the additive coverage is destroyed.

[0016] Preferably, in the above technical scheme, the water-soluble additive is a mixture of macromolecules and small molecules, the macromolecule is one or more of hydrolyzed protein peptides, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, cellulose ether, polyvinyl alcohol, polyethylene glycol, gelatin, poly(3,4-ethylenedioxythiophene) poly(styrene sulfonate) polyaniline, and the small molecule is one or more of sodium 3-mercapto-1-propane sulfonate, sodium polydisulfide propane sulfonate, sodium 3-(benzothiazole-2-mercapto)-propane sulfonate, isothiourea propanesulfonic acid inner salt, sodium allyl sulfonate, benzotriazole, 2-mercaptobenzothiazole, and 2-mercaptobenzimidazole.

[0017] Preferably, in the above technical solution, a water-soluble additive solution I is prepared, and can be heated or stirred at room temperature according to the solubility of the additive molecules.

[0018] Preferably, in the above technical solution, the concentration of the salt solution II is 0.01 mol / L to 5 mol / L.

[0019] Preferably, in the above technical solution, the conductive material V is a plate or a mesh structure, and is selected from one of platinum, carbon, titanium, stainless steel, copper, platinum, gold, silver, nickel and alloys thereof.

[0020] Preferably, in the above technical solution, the electrolysis current in step d is 0.01A / dm 2 ~30A / dm 2 , the electrolysis time is 1s~20min, and the temperature is 20~70℃.

[0021] Preferably, in the above technical solution, in the electrolysis step d, the electrolyte may be static or dynamic, and the flow mode of the dynamic electrolyte may be one of air disturbance, circulating pump, and stirring.

[0022] When electrolysis is performed, if aluminum (Al) is used as the anode and connected to the positive electrode of the power supply, the aluminum will lose electrons to form aluminum ions under the action of the applied current. At the same time, under the influence of the electric field, the ions in the solution will migrate, and the combined effect will cause holes to form on the aluminum surface.

[0023] Under static conditions without an applied voltage, the ions in the solution can only reach the aluminum surface by diffusion, which is a slow process. When stirring or a circulating pump is used to make the solution dynamic, the ions can move by diffusion and convection, which speeds up the movement of the ions and thus accelerates the reaction process.

[0024] In short, when no electricity is applied in a dynamic solution, the movement of ions includes diffusion and convection; while when electrolysis is performed in a dynamic solution, it includes three modes of movement: diffusion, convection, and migration. Therefore, the two main functions of applying voltage are: one is to promote the rapid movement of ions, thereby accelerating the reaction rate; the other is to force aluminum to lose electrons and dissolve through an external power supply.

[0025] Diffusion refers to the process by which ions achieve uniform distribution through random motion in the absence of macroscopic flow, and is driven by concentration gradients.

[0026] Convection refers to the movement of ions due to the macroscopic flow of a solution or medium, which can be caused by factors such as temperature gradients or pressure differences.

[0027] Migration refers to the process in which ions move in a directional manner along the direction of the electric field under the action of an external electric field.

[0028] Preferably, in the above technical solution, the additive solution I in step a can also be first coated on the surface of the aluminum foil to form a film, and then the aluminum foil after the film is immersed in the salt solution II to perform steps d and e.

[0029] An aluminum foil with a microporous structure obtained by the above-mentioned preparation method, wherein the aluminum foil is a rolled aluminum foil,

[0030] The micropores have a pore size of 0-150 μm, and the micropores include blind holes and through holes.

[0031] Preferably, in the above technical solution, the pore size is 0.4-50um, and the pore density is 2000-20000 / cm 2 , the hole depth is 1-10um.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The electrochemical method for preparing microporous aluminum foil in this patent has many significant advantages. First, the method can accurately control the pore size of the micropores to 0.4-50um and the pore density to 2000-25000 / cm2 , the hole depth is 1-10um, which can meet various specific needs in different application scenarios. Secondly, compared with traditional preparation methods, this technology has higher production efficiency, can significantly shorten the production cycle (see the table below for details), and improve production capacity and product supply response speed. In addition, this method is flexible and can adjust process parameters according to user needs, thereby realizing customized production and adapting to diverse market needs. Description of the drawings:

[0034] Figure 1 This is an electron microscope image of the pore-forming surface of aluminum foil. Specific implementation method:

[0035] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0036] A method for preparing an aluminum foil with a microporous structure, the specific steps are as follows:

[0037] a. A water-soluble additive and water are mixed in a predetermined ratio to prepare a water-soluble additive solution I, wherein the water-soluble additive solution I contains macromolecules and small molecules of amino, hydroxyl, thiol, carboxyl, ether bond, aldehyde, and nitrogen-containing functional groups, wherein the macromolecule refers to a molecule with a molecular weight greater than 1000, and the small molecule refers to a molecule with a molecular weight less than 1000; the water-soluble additive solution I is prepared, and heating or stirring at room temperature can be performed according to the solubility of the additive molecules. The water-soluble additive is a mixture of macromolecules and small molecules. The macromolecule is one or more of hydrolyzed protein peptides, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, cellulose ether, polyvinyl alcohol, polyethylene glycol, gelatin, poly(3,4-ethylenedioxythiophene) poly(styrene sulfonate) polyaniline; the small molecule is one or more of sodium 3-mercapto-1-propane sulfonate, sodium polydisulfide propane sulfonate, sodium 3-(benzothiazole-2-mercapto)-propane sulfonate, isothiourea propanesulfonic acid inner salt, sodium allyl sulfonate, benzotriazole, 2-mercaptobenzothiazole, and 2-mercaptobenzimidazole.

[0038] b. Prepare a salt solution II of a certain concentration; the salt solution II is a salt aqueous solution that can provide conductive ions, selected from one of sodium chloride, potassium bromide, potassium perchlorate, and potassium sulfate; or a compound that can react with Al, selected from one of cupric chloride, ferric chloride, potassium hydroxide, hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, formic acid, oxalic acid, and chloroacetic acid; the concentration of the salt solution II is 0.01 mol / L to 5 mol / L.

[0039] c. Mixing solution I and salt solution II in a certain proportion to form electrolyte III for preparing microporous aluminum foil in the next step, wherein the concentration of the water-soluble additive in the solution is 1-500 ppm after mixing;

[0040] d. Immerse the original aluminum foil IV in the electrolyte III as an anode, immerse the conductive material V in the electrolyte III as a cathode, and load an appropriate current for electrolysis; the electrolysis current in step d is 0.01A / dm 2 ~30A / dm 2 , the electrolysis time is 1s to 20min, and the temperature is 20 to 70°C. In the electrolysis step d, the electrolyte can be static or dynamic, and the flow mode of the dynamic electrolyte can be one of air disturbance, circulating pump, and stirring. When electrolysis is performed, if aluminum (Al) is used as the anode and connected to the positive electrode of the power supply, under the action of the applied current, the aluminum will lose electrons to form aluminum ions. At the same time, under the influence of the electric field, the ions in the solution will migrate, and the combined effect will cause holes to form on the aluminum surface.

[0041] Examples

[0042]

[0043] Under static conditions without an applied voltage, the ions in the solution can only reach the aluminum surface by diffusion, which is a slow process. When stirring or a circulating pump is used to make the solution dynamic, the ions can move by diffusion and convection, which speeds up the movement of the ions and thus accelerates the reaction process.

[0044] In short, when no electricity is applied in a dynamic solution, the movement of ions includes diffusion and convection; while when electrolysis is performed in a dynamic solution, it includes three modes of movement: diffusion, convection, and migration. Therefore, the two main functions of applying voltage are: one is to promote the rapid movement of ions, thereby accelerating the reaction rate; the other is to force aluminum to lose electrons and dissolve through an external power supply.

[0045] Diffusion refers to the process by which ions achieve uniform distribution through random motion in the absence of macroscopic flow, and is driven by concentration gradients.

[0046] Convection refers to the movement of ions due to the macroscopic flow of a solution or medium, which can be caused by factors such as temperature gradients or pressure differences.

[0047] Migration refers to the process in which ions move in a directional manner along the direction of the electric field under the action of an external electric field.

[0048] The conductive material V is a plate or a mesh structure, and is selected from one of platinum, carbon, titanium, stainless steel, copper, platinum, gold, silver, nickel and alloys thereof.

[0049] e. After electrolysis for a specific period of time, the aluminum foil IV is taken out, cleaned and dried to obtain a microporous aluminum foil V.

[0050] When aluminum foil is immersed in solution III, the additive molecules can be adsorbed on the surface of the foil. Additives with larger molecular weights can be evenly adsorbed on the surface of aluminum by virtue of functional groups such as hydroxyl, amino, carboxyl, and thiol. Additives with smaller molecular weights can be adsorbed with macromolecules to supplement the surface space of the foil, thereby achieving coverage of the foil surface. During electrolysis, the foil acts as an anode. Under the action of an applied current / voltage, aluminum loses electrons to generate aluminum ions, and the additive coverage on a small part of the foil surface is destroyed, thereby generating holes. When the solution contains Cl - 、F - When there are anions, these ions have a small radius and strong penetration, which can easily destroy the oxide film and produce corrosion holes. By controlling the type, molecular weight, concentration of additives, as well as the electrolyte composition, concentration, pH, temperature, current density, voltage and electrolysis time, microporous aluminum foil with different pore sizes and pore structures can be obtained.

[0051] The pore size is related to the molecular weight and concentration of the additive. The larger the molecular weight and the higher the concentration, the smaller the pore size. The pore depth is related to the concentration of ions in the solution, temperature, reaction time, and current / voltage. The greater the ion concentration, the higher the temperature, the longer the reaction time, and the higher the current / voltage, the deeper the pore depth. The pore density is related to the additive concentration, the salt ion concentration, and the current / voltage. The smaller the additive concentration, the higher the salt ion concentration and the current / voltage, the greater the pore density. The higher the concentration of H+, OH- or oxidizing ions such as Cu2+, the faster the reaction rate.

[0052] The concentration of ions reacting with Al in the solution and the size of the applied current / voltage are related to the degree of damage to the additive coverage. When the total concentration of ions that can react with Al in the solution is 0.01mol / L-5mol / L and the applied current density is 1-15A / dm2, 0.2%-30% of the additive coverage is destroyed.

[0053] As an alternative technical solution, the additive solution I in step a can also be first coated on the surface of the aluminum foil to form a film, and then the film-formed aluminum foil is immersed in the salt solution II to perform steps d and e.

[0054] An aluminum foil with a microporous structure obtained by the above-mentioned preparation method, wherein the aluminum foil is a rolled aluminum foil, the pore size is 0.4-50um, and the pore density is 2000-20000 / cm 2 , the hole depth is 1-10um. Micropores include blind holes and through holes. Blind hole aluminum foil means that the holes on the aluminum foil do not penetrate the entire foil, but only form holes of a certain depth on the surface. Through hole aluminum foil means that the holes penetrate the foil deeply.

[0055] The electrochemical method for preparing microporous aluminum foil in this patent has many significant advantages. First, this method can accurately control the pore size of the micropores at 0.4-50um, the pore density at 2000-25000 / cm2, and the pore depth at 1-10um, so that it can meet various specific needs in different application scenarios. Secondly, compared with traditional preparation methods, this technology has higher production efficiency, can significantly shorten the production cycle (see the table below for details), and improve production capacity and product supply response speed. In addition, this method is flexible and can adjust process parameters according to user needs, thereby realizing customized production and adapting to diverse market needs.

[0056]

[0057] In addition, the electrochemical preparation of microporous aluminum foil does not require the use of harmful chemicals, does not pollute the environment, and meets environmental protection requirements. The operation process is simple and easy to control, which can reduce human errors and improve production stability and consistency.

[0058] The electrochemical preparation method of microporous aluminum foil developed in this patent not only breaks through many technical limitations of traditional preparation methods, but also shows obvious advantages in environmental protection, production efficiency and product quality stability.

[0059] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for preparing an aluminum foil having a microporous structure, characterized in that: The specific steps are as follows: a. A water-soluble additive and water are mixed in a predetermined ratio to prepare a water-soluble additive solution I, wherein the water-soluble additive solution I contains macromolecules and small molecules having amino, hydroxyl, thiol, carboxyl, ether bond, aldehyde, and nitrogen-containing functional groups, wherein the macromolecule refers to a molecule having a molecular weight greater than 1000, and the small molecule refers to a molecule having a molecular weight less than 1000; b. Prepare a salt solution II of a certain concentration; the salt solution II is a salt aqueous solution providing conductive ions, selected from one of sodium chloride, potassium bromide, potassium perchlorate, and potassium sulfate; or a compound that reacts with Al, selected from one of cupric chloride, ferric chloride, potassium hydroxide, hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, formic acid, oxalic acid, and chloroacetic acid; c. Mixing solution I and salt solution II in a certain proportion to form electrolyte III for preparing microporous aluminum foil in the next step, wherein the concentration of the water-soluble additive in the solution is 1-500 ppm after mixing; d. Immerse the original aluminum foil IV in the electrolyte III as an anode, immerse the conductive material V in the electrolyte III as a cathode, and load an appropriate current for electrolysis; e. After the electrolysis is performed for a specific period of time, the aluminum foil IV is taken out, cleaned and dried to obtain a microporous aluminum foil.

2. The method for preparing an aluminum foil having a microporous structure according to claim 1, characterized in that: The water-soluble additive is a mixture of macromolecules and small molecules. The macromolecule is one or more of hydrolyzed protein peptides, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, cellulose ether, polyvinyl alcohol, polyethylene glycol, gelatin, poly(3,4-ethylenedioxythiophene) poly(styrene sulfonate) polyaniline; the small molecule is one or more of sodium 3-mercapto-1-propane sulfonate, sodium polydisulfide propane sulfonate, sodium 3-(benzothiazole-2-mercapto)-propane sulfonate, isothiourea propanesulfonic acid inner salt, sodium allyl sulfonate, benzotriazole, 2-mercaptobenzothiazole, and 2-mercaptobenzimidazole.

3. The method for preparing the aluminum foil with a microporous structure according to claim 1, characterized in that: A water-soluble additive solution I is prepared, and the solution may be heated or stirred at room temperature according to the solubility of the additive molecules.

4. The method for preparing an aluminum foil having a microporous structure according to claim 1, characterized in that: The concentration of salt solution II is 0.01 mol / L to 5 mol / L.

5. The method for preparing an aluminum foil having a microporous structure according to claim 1, characterized in that: The conductive material V is a plate or a mesh structure, and is selected from platinum, carbon, titanium, stainless steel, copper, platinum, gold, silver, nickel and alloys thereof.

6. The method for preparing an aluminum foil having a microporous structure according to claim 1, characterized in that: The electrolysis current in step d is 0.01A / dm 2 ~30A / dm 2 , the electrolysis time is 1s~20min, and the temperature is 20~70℃.

7. The method for preparing an aluminum foil having a microporous structure according to claim 1, characterized in that: The additive solution I in step a can also be first coated on the surface of the aluminum foil to form a film, and then the aluminum foil after the film is immersed in the salt solution II to perform steps d and e.

8. The method for preparing an aluminum foil having a microporous structure according to claim 1, characterized in that: In the electrolysis step d, the electrolyte may be static or dynamic, and the flow mode of the dynamic electrolyte may be one of air disturbance, circulating pump, and stirring.

9. An aluminum foil with a microporous structure obtained by the preparation method according to claim 1, characterized in that: The aluminum foil is a rolled aluminum foil, the micropores have a pore size of 0-150 μm, and the micropores include blind holes and through holes.

10. The aluminum foil according to claim 9, characterized in that: The pore size is 0.4-50um, and the pore density is 2000-20000 / cm 2 , the hole depth is 1-10um.

Citation Information

Cited By

  • Preparation method of SMD (Surface Mount Device) solid-liquid mixed aluminum electrolytic capacitor

    CN120108937A